Contribuições para a configuração de um modelo de competências para incubadoras de empresas de base tecnológica - Genilton Sant´Anna, Antonio; França Versiani, Ângela (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Business incubators are entrepreneurships that aim to provide an effective way for the incubated companies survive in actual dynamic and turbulent business environment. In this sense many studies have been developed on the subject. In turn, the notion of organizational competence while concept, application or impacts on organizations, has also been the subject of numerous studies. This study aims to contribute to the setting of a competency model for incubators of technology- based companies, given the apparent lack of an exclusive work in this direction. The conclusion shows the initial configuration of an organizational competence model for incubators of technology-based companies. Despite a theoretical contribution does not necessarily imply an immediate intervention in reality, it is expected that this will serve as a basis for new contributions to the subject.
Keywords: Business incubators; Organizational competence; Competency model